Clinical profiling of MRD48 and functional characterization of two novel pathogenic RAC1 variants - Priolo, Manuela; Zara, Erika; Radio, Francesca Clementina; Ciolfi, Andrea; Spadaro, Francesca; Bellacchio, Emanuele; Mancini, Cecilia; Pantaleoni, Francesca; Cordeddu, Viviana; Chiriatti, Luigi; Niceta, Marcello; Africa, Emilio; et al. (European journal of human genetics : EJHG, 2023)
RAC1 is a member of the Rac/Rho GTPase subfamily within the RAS superfamily of small GTP-binding proteins, comprising 3 paralogs playing a critical role in actin cytoskeleton remodeling, cell migration, proliferation and differentiation. De novo missense variants in RAC1 are associated with a rare neurodevelopmental disorder (MRD48) characterized by DD/ID and brain abnormalities coupled with a wide range of additional features. Structural and functional studies have documented either a dominant negative or constitutively active behavior for a subset of mutations. Here, we describe two individuals with previously unreported de novo missense RAC1 variants. We functionally demonstrate their pathogenicity proving a gain-of-function (GoF) effect for both. By reviewing the clinical features of these two individuals and the previously published MRD48 subjects, we further delineate the clinical profile of the disorder, confirming its phenotypic variability. Moreover, we compare the main features of MRD48 with the neurodevelopmental disease caused by GoF variants in the paralog RAC3, highlighting similarities and differences. Finally, we review all previously reported variants in RAC proteins and in the closely related CDC42, providing an updated overview of the spectrum and hotspots of pathogenic variants affecting these functionally related GTPases.